Chapter 1 Examining the illusion of accountability - Karlsson, Christer (Taylor & Francis, 2009)
Do EU citizens have real opportunities to hold decision-makers accountable, or does the current institutional set-up in the Union merely create an illusion of accountability? That is the central question of this volume. There are widespread and growing concerns that the political system of the EU does not, in fact, afford citizens appropriate mechanisms of accountability. The aim of the current study is to ascertain whether such concerns are warranted.